Semaphorins and Their Receptors: From Axonal Guidance to Atherosclerosis - Hu, Shuhong; Zhu, Li (Frontiers in Physiology, 2018)
Abstract Semaphorins are a large family of secreted, transmembrane, or GPI-anchored proteins initially identified as axon guidance cues signaling through their receptors, neuropilins and plexins. Emerging evidence suggests that beyond the guidance, they also function in a broad spectrum of pathophysiological conditions, including atherosclerosis, a vascular inflammatory disease. Particular semaphorin members have been demonstrated to participate in atherosclerosis via eliciting endothelial dysfunction, leukocyte infiltration, monocyte-macrophage retention, platelet hyperreactivity and neovascularization. In this review, we focus on the role of those semaphorin family members in the development of atherosclerosis and highlight the mechanistic relevance of semaphorins with atherogenesis.